Hepatitis B Vaccination Practices among At-Risk Adults in Six European Countries - Quang Vinh Nguyen (2014)
Background: Countries in Western and Northern Europe are categorized as low prevalence countries with hepatitis B. However the problems with hepatitis B infection are increasingly recognized, especially among distinct groups of adults. For instance, new infections are concentrated in injecting drug users, inmates, and immigrants from high endemic regions. Vaccination is the best way to prevent hepatitis B infection and its consequences. At-risk adults are recommended to receive this vaccination. This study aims to analyze the current vaccination practices (regarding provision, copayment, and responsibility) for various groups of at-risk individuals in six European countries: the United Kingdom, Germany, Netherlands, Hungary, Italy and Spain. Methods: Online questionnaires were carried out in the six countries. In total 1181 experts from six different health professions (public health professionals, general practitioners, sexual health service providers, health specialists, antennal care providers and asylum seeker care providers) were invited to participate. The collected data was analyzed with IBM SPSS Statistics 21 software. Results: The surveys were completed by 286 respondents. In general, the vaccination practices for at-risk individuals greatly vary among the countries. And, within the country, the practices greatly differ between health professionals. Generally, the majority of the respondents in most of the countries stated that hepatitis B vaccination is either being given commonly or sometimes and free of charge to prioritized at-risk groups (such as IDUs, sex workers, MSM, HIV positive patients, and contacts of positive hepatitis B patients). There were considerable matches between the current practices and the current national polices (guidelines or recommendations) for some at-risk groups in some countries. However, to some degree, gaps between the practices and the policies for certain at-risk groups in some countries were observed.